SEROLOGICAL AND MOLECULAR EVALUATION OF MRP14 IN THYROIDITIS AND ITS ROLE IN PRO-INFLAMMATORY CHEMOKINES ACTIVATION - Hussein, Aya M.; Al Sahlanee, Rasha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the involvement of Myeloid Related Protein 14 (MRP14) in the production of CXC Motif Chemokine Ligand 9 (CXCL9) in thyroiditis patients. The first group composed of 27 hypothyroidism (HO) patients (12 men and 15 women), age average about 46 years old. The second group had 43 patients (8 men and 35 women) with hyperthyroidism (HR), their mean of age was 42, while 30 healthy persons act as control group (HC) had an average age of 33.47 of men (13) and women (17). The three groups were testing for triiodothyronine (T3), thyroxine (T4) and thyroid stimulating hormone (TSH) furthermore, testing the thyroglobulin (TG), anti-thyroperoxidase (a-TPO), anti-TSH receptor (TSHR) and serum level of MRP14 by Enzyme-Linked Immunosorbent Assay (ELISA). The results showed a high significant (P< 0.0001) increase in MRP14 levels in hypothyroid group vs hyperthyroidism 123.1 ± 22.39 and 109.8 ± 4.479 ng/ml respectively. MRP14 showed a positive correlation with T4 and a negative correlation with anti-TSHR in HR patients. The gene expression of MRP14 and CXCL9 were assayed to all groups by RT-PCR, results showed a high expression of MRP14 as well as of CXCL9 in the patient groups which showed a high expression of CXCL9 in HO patients. Therefore, the results obtained from the study indicate that the higher concentration of MRP14 expression in Thyroiditis patients might play an important role in the development of the disease mediated by stimulating the secretion of pro-inflammatory chemokines.